GPR34 Stabilized by Deubiquitinase USP8 Suppresses Ferroptosis of ATC - Bokang Yan; Jiaxing Guo; Meiyuan Huang; Zhecheng Li; Jingyue Sun; Hailong Tan; Weiwei Lai; Shi Chang (Mediators of Inflammation)
G protein-coupled receptor 34 (GPR34) is an orphan receptor within the G protein-coupled receptor (GPCR) superfamily, and its specific role in anaplastic thyroid carcinoma (ATC) remains to be elucidated. In this study, we observed that GPR34 was aberrantly upregulated in ATC and the deletion of GPR34 inhibited tumor progression both in vivo and in vitro. Additionally, suppression of GPR34 promoted ferroptosis in ATC cells. We further identified USP8 as a deubiquitinase (DUB) for GPR34, and the effects induced by GPR34 deletion were reversible through USP8 overexpression. Moreover, targeting USP8 with the inhibitor DUB-IN-3 effectively restrained ATC growth. Together, the present study revealed the role of GPR34 in ATC progression and ferroptosis, discovered its corresponding DUBs, and proposed GPR34 as a promising target for ATC therapy.